Natural elements spatial configuration and content usage in urban park - Hami, Ahmad; Maulan, Suhardi; Mariapan, Manohar; Malekizadeh, Mohammad (Iran University of Science and Technology, 2014)
Urban parks are important public multifunctional space used for a wide range of activities. The usage levels of parks depend on the spatial characteristics of the spaces, where its forms and occupancies are referred as the usage-spatial relationship. Natural elements spatial complexity and park usability is of interest in this study. A photo - questionnaire was conducted among 296 of park users in Tabriz, Iran to gauge the relationship between park usability dimensions and natural elements complexity levels. The result revealed three dimensions for park usability namely social activities, passive nature activities, and nature appreciation where passive nature activities received the highest preference. The results from SEM models addressed non-significant relationship between park usability and high complexity level of natural elements; meanwhile there was a significant positive relationship between social activities and moderate complexity of natural elements. A negative significant relationship of nature appreciation and positive relationship of social activities with low complex natural elements were observed. Landscape designers should avoid suggesting crowded planting areas (high complexity), which obstruct visibility in urban park and probably reduce perceived safety. It seems that water features show positive effect on people’s desire to do activities in urban park. Spatial configuration of vegetation contributed in park usability level and a safe feeling in urban park which might be necessary for future researches.